The design of active site inhibitors of Mycobacterium tuberculosis tyrosyl-tRNA synthetase based on SB-219383 inhibitor - Mykuliak, V.V.; Dubey, I.Ya.; Kornelyuk, A. I. (Reports of the National Academy of Sciences of Ukraine, 2014)
Mycobacterium tuberculosis tyrosyl-tRNA synthetase (MtTyrRS) is one of the key enzymes at the pre-ribosomal protein synthesis step and its inhibition should significantly suppress the growth of pathogenic bacteria in the host body. MtTyrRS and human TyrRS are not able to cross-recognition and aminoacylation of cognate tRNATyr, therefore the specific inhibitors of MtTyrRS should not be toxic to human body. Interactions between the inhibitor and the KMSKS-like catalytic loop of MtTyrRS should significantly increase its affinity to the enzyme. We have performed the design of new inhibitors of MtTyrRS based on the structure of the known SB-219383 inhibitor. We modified the inhibitor in order to allow its interactions with the catalytic loop of MtTyrRS. The 100-ns dynamics of MtTyrRS reveals that the proposed inhibitors interact with the catalytic loop during the simulation.